2019
DOI: 10.1039/c9ra05558d
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise engineering ofSaccharomyces cerevisiaeto produce (+)-valencene and its related sesquiterpenes

Abstract: A new yeast-based platform for the biosynthesis of (+)-valencene and its related sesquiterpenes found in grapefruit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 47 publications
0
28
1
Order By: Relevance
“…These results were consistent with previous reports that the lower incubation temperature was beneficial for valencene accumulation. 68…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were consistent with previous reports that the lower incubation temperature was beneficial for valencene accumulation. 68…”
Section: Resultsmentioning
confidence: 99%
“…These results were consistent with previous reports that the lower incubation temperature was beneficial for valencene accumulation. 68 To facilitate mannitol assimilation by yeast, the uptake rate and metabolic efficiency of mannitol need to be enhanced. As a result, the mannitol dehydrogenase coding gene DSF1 and mannitol transporter coding gene HXT13 under the control of the strong promoters P SED1L and P CDC19 were integrated into the genome of strain BN-913A.…”
Section: Characteristics Of Valencene Production By S Cerevisiae Duri...mentioning
confidence: 99%
“…Different enzymes responsible for many microbial activities are also sensitive to high temperatures and are usually inactivated in this harsh condition [ 103 ]. Moreover, the role of temperature in (+)-valencene accumulation was investigated and found that remarkable enhancement in (+)-valencene concentration at 25 °C (87.2 mg/L) was observed compared to at 30 °C (20.6 mg/L) [ 21 ]. The benefit of lowering the temperature in the production of other relevant pharmaceuticals in yeast has also been previously reported in the case of plant lectins expression in Pichia pastoris [ 104 , 105 ].…”
Section: Factors Affecting Fermentation Process Of Pharmaceutical Terpenoidsmentioning
confidence: 99%
“…In the same line, S. cerevisiae has emerged as a model organism for the production of terpenoids since it has many additional advantages other than mentioned above, such as generally regarded as safe (GRAS) status, high genetic tractability, ease of manipulation, possessing universal endogenous MVA pathway, ability to express eukaryotic cytochrome P450 enzymes, robustness, relatively absence of secondary metabolites, high sugar catabolic, fast growth rate, and high tolerance against harsh industrial conditions [ 7 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Related research has used S. cerevisiae as the host strain to reconstruct its metabolic pathway in vivo and biosynthesize (+)-valencene and its derivatives (+)-nootkatone. Finally, the synthesis of (+)-nootkatone reached 53.7 mg/l through resting cell transformation (Ouyang et al, 2019 ). Recently, a biosynthetic pathway was constructed in S. cerevisiae to produce the (+)-nootkatone by overexpressing the CnVS, HPO, and ZSD1 combined with the MVA pathway engineering.…”
Section: Synthesis Of (+)-Nootkatone By Heterologous Synthesismentioning
confidence: 99%